Cannabinoid hyperemesis syndrome: genetic susceptibility to toxic exposure - Russo, Ethan B.; Whiteley, Venetia L. (Frontiers in Toxicology, 2024)
Cannabinoid hyperemesis syndrome presents as a complex of symptoms and signs encompassing nausea, vomiting, abdominal pain, and hot water bathing behavior, most typically in a heavy cannabis user. Its presentation is frequently associated with hypothalamic-pituitary-adrenal axis activation with stress and weight loss. Recent investigation has identified five statistically significant mutations in patients distinct from those of frequent cannabis users who lack the symptoms, affecting the TRPV1 receptor, two dopamine genes, the cytochrome P450 2C9 enzyme that metabolizes tetrahydrocannabinol, and the adenosine triphosphate-binding cassette transporter. The syndrome is associated with escalating intake of high potency cannabis, or alternatively, other agonists of the cannabinoid-1 receptor including synthetic cannabinoids. Some patients develop environmental triggers in scents or foods that suggest classical conditioned responses. Various alternative “causes” are addressed and refuted in the text, including exposure to pesticides, neem oil or azadirachtin. Nosological confusion of cannabinoid hyperemesis syndrome has arisen with cyclic vomiting syndrome, whose presentation and pathophysiology are clearly distinct. The possible utilization of non-intoxicating antiemetic cannabis components in cannabis for treatment of cannabinoid hyperemesis syndrome is addressed, along with future research suggestions in relation to its genetic foundation and possible metabolomic signatures.